Poly(ethylene glycol) Diacrylate Hydrogels Doped with Silver Nanoparticles for Optical Sensing and Removing Hg(II) Ions from Water - Luca Burratti; Michele Sisani; Irene Di Guida; Fabio De Matteis; Roberto Francini; Paolo Prosposito (Chemosensors, 2023)
In this study, an innovative approach for the integration of silver nanoparticles (AgNPs) into poly(ethylene glycol) diacrylate (PEGDA) hydrogels is described. The composite material is the first in the literature where AgNPs were doped into PEGDA using photo-polymerization technique for a double function: detection and elimination of Hg(II) ions from water. The doping of AgNPs into PEGDA-based matrices was performed using a photo-polymerizable process. The Hg(II) sensing properties were explored in a concentration range from 0 to 20 mg/L. Notably, a linear dependence was observed up to 1 mg/L, accompanied by a limit of detection of 0.3 mg/L. Beyond sensing, the efficiency of the doped hydrogel in removing Hg(II) ions was also investigated and compared with an undoped PEGDA matrix. The outcome highlighted an enhanced removal efficiency of the doped material of approximately 23%. Finally, the experimental data suggested that the interaction between Hg(II) ions and the modified hydrogel adhered to the Langmuir isotherm model, which suggested that chemisorption was the driving mechanism of the adsorption of Hg(II) onto the modified hydrogel matrix.